Reducing Implicit Gender Leadership Bias in Academic Medicine With an Educational Intervention. (August 2016) - Girod, Sabine; Fassiotto, Magali; Grewal, Daisy; Ku, Manwai Candy; Sriram, Natarajan; Nosek, Brian A.; Valantine, Hannah
Abstract : Purpose: One challenge academic health centers face is to advance female faculty to leadership positions and retain them there in numbers equal to men, especially given the equal representation of women and men among graduates of medicine and biological sciences over the last 10 years. The purpose of this study is to investigate the explicit and implicit biases favoring men as leaders, among both men and women faculty, and to assess whether these attitudes change following an educational intervention. Method: The authors used a standardized, 20-minute educational intervention to educate faculty about implicit biases and strategies for overcoming them. Next, they assessed the effect of this intervention. From March 2012 through April 2013, 281 faculty members participated in the intervention across 13 of 18 clinical departments. Results: The study assessed faculty members' perceptions of bias as well as their explicit and implicit attitudes toward gender and leadership. Results indicated that the intervention significantly changed all faculty members' perceptions of bias ( P < .05 across all eight measures). Although, as expected, explicit biases did not change following the intervention, the intervention did have a small but significant positive effect on the implicit biases surrounding women and leadership of all participants regardless of age or gender ( P = .008). Conclusions: These results suggest that providing education on bias and strategies for reducing it can serve as an important step toward reducing gender bias in academic medicine and, ultimately, promoting institutional change, specifically the promoting of women to higher ranks. Abstract : Supplemental Digital Content is available in the text.